MIGRANTS: IDENTITIES AND BORDERS MANAGEMENT - Bessa, F.; Malheiro, L. (15th biennial conference of ERGOMAS (European Research Group on Military and Society), Lisbon, Portugal, 17-21 June 2019, 2019)
Considering the tension created by thousands of migrants who have elected Europe with the aim to find a better place to live and work, which is connected or has been connected with several terrorist attacks and the perpetration of terror acts in several European cities, we were very curious to understanding the diversity of discourses that have been built around this human massive migration. Additionally, we thought that it was very important to deconstruct biased speeches and misperceptions of this reality. So, with the present paper, we aim to answer the following question: what are the main characteristics of the migrants who have entered in Europe? Consequently, we were interested in recognizing which are the principal European borders management actors, as an important asset to better understand what kind of actions have been taken and what kind of actions could be taken to answer humanely and positively to the present massive waves of people from different countries, namely from Africa, to Europe, allowing authorities to provide accurate legislation, as well as to increase the interdisciplinary analysis and dialogue as it will be impossible to find a local and individual answer for a global problem. Finally, it is our intention to finish the investigation producing knowledge and innovative tools that can help to better understand this migration flow, especially those that are affecting border management and control.